Guidelines of the European Respiratory Society and the European Society of Thoracic Surgeons for the management of malignant pleural mesothelioma - Scherpereel, Arnaud; Astoul, P.; Baas, P.; Berghmans, T.; Clayson, H.; Vuyst, P. de; Dienemann, Hendrik; Galateau-Salle, F.; Hennequin, C.; Hillerdal, G.; Péchoux, C. Le; Mutti, L.; et al. (The European respiratory journal, 2010)
Malignant pleural mesothelioma (MPM) is a rare tumour but with increasing incidence and a poor prognosis. In 2008, the European Respiratory Society/European Society of Thoracic Surgeons Task Force brought together experts to propose practical and up-to-dated guidelines on the management of MPM. - To obtain an earlier and reliable diagnosis of MPM, the experts recommend performing thoracoscopy, except in cases of pre-operative contraindication or pleural symphysis. The standard staining procedures are insufficient in ∼10% of cases. Therefore, we propose using specific immunohistochemistry markers on pleural biopsies. In the absence of a uniform, robust and validated staging system, we advice use of the most recent TNM based classification, and propose a three step pre-treatment assessment. Patient's performance status and histological subtype are currently the only prognostic factors of clinical importance in the management of MPM. Other potential parameters should be recorded at baseline and reported in clinical trials. MPM exhibits a high resistance to chemotherapy and only a few patients are candidates for radical surgery. New therapies and strategies have been reviewed. - Because of limited data on the best combination treatment, we emphasise that patients who are considered candidates for a multimodal approach should be included in a prospective trial at a specialised centre.
Online veröffentlicht am 28. August 2009
Gesehen am 06.06.2023